PENERAPAN METODE MODIFIKASI ANDERSEN DALAM PENILAIAN RISIKO BENDUNGAN HALIWEN: ANDERSEN MODIFICATION METHOD APPLICATION IN HALIWEN DAM RISK ASSESSMENT - Maulana, Muhammad Fuad; Sukamta; Dyah Ari Wulandari (Universitas Muhammadiyah Surabaya, 2024)
Indonesia is a disaster-prone country; therefore, all infrastructure must be risk-analyzed in order to carry out mitigation efforts. One of the infrastructures that holds the potential for high risk of danger is a dam. Dams need to be inspected regarding dam operations, maintenance, and safety, one of which is through regular inspections. The results of the inspection can be used to analyze dam risks. The Haliwen Dam was originally a reservoir whose classification was upgraded to dam due to the enactment of Minister of Public Works Regulation No. 27 of 2015 concerning Dams. The Haliwen Dam needs to be analyzed for its risks as a dam. The method for analyzing the risk of dams can use the modified Andersen method. This method works well for dams with limited information during construction and instrumentation. This research requires a report on the results of field inspections to determine the physical condition of the dam. The end result of this analysis is the dam risk condition in the form of a safety value (Naman). The safety value obtained is 80. Based on the risk assessment of the modified Andersen method, the Haliwen Dam has a safety value above 75 (satisfactory), which means that the dam is in good condition and has a low risk of failure. A satisfactory safety value means that the dam can operate properly at ordinary (normal) and extraordinary load times.